Estimating benthic trophic levels to assess the effectiveness of marine protected area management - Blanco, Andreu; Beger, Maria; Planes, Serge; Miller, Mark; Olabarria, Celia (The Science of the total environment, 2021)
Designating and managing marine protected areas (MPAs) can mitigate many ocean threats. Banning fishing activities within MPAs enhances the robustness of food-web dynamics and thus increases trophic resilience. Ecosystem function indicators, such as mean trophic level, are increasingly applied in conservation management. Stable isotope analysis is a common tool in trophodynamic studies as it provides information about food sources and trophic level within food webs. In contrast to the traditional top-down approaches in conservation management (mainly for fisheries), this study focuses on bottom-up responses to protection according to the target species in regional small-scale fisheries. The present study aimed to examine how MPA status affects trophodynamics in the rocky reefs of the Illas Atlánticas Marine-Terrestrial National Park (Galicia, NW Spain). Results showed no differences between inside and outside the MPA in species stable isotopic signatures or trophic level. However, these results should be considered with caution due to some limitations in the study design (small number of sites per location, biogeographic differences associated with the island nature of the MPA, or seasonal variability). Nevertheless, the lax fishing management, the lack of proper implementation (the MPA was established in 2002 without a management plan until 2019), and the small size of the studied MPA may result in ineffective conservation outcomes that could have been reflected in the stable isotopic content of the food web. The large number of “paper park” MPAs existing worldwide are not only detrimental to the perception of marine protection, but also provide poor protection of marine ecosystems. Subject to further studies accounting for both environmental and management factors on stable isotope signatures, trophic interactions can form a cost-effective tool for monitoring MPA effectiveness. [Display omitted] •Bottom up effects of MPAs on trophic level are often ignored.•Trophodynamics inside/outside MPAs can be assessed by stable isotopes analysis.•Protection did not significantly affect trophic level in Illas Atlánticas MPA.•Trophic levels in MPAs vary across locations but not across management regimes.•Poorly managed MPAs do not appear to have protective effects on food web dynamics.